Biodegradable films with lactic acid polyesters shunted with nitrogen components

By adding specific nitrogen compounds or linear amines to PLA as fluidizing additives, the shear viscosity of PLA is solved, and the problem that existing packaging films are difficult to achieve mechanical properties, optical transparency and biodegradability at the same time is achieved, and a packaging film with high transparency and good performance is achieved.

CN119836450APending Publication Date: 2025-04-15NOVAMONT SPA
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380062881.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-27
Filing Date
2023-07-21
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

Existing biodegradable packaging films are difficult to achieve good mechanical properties, optical transparency and biodegradability at the same time, especially when using viscous PLA, transparency is often affected.

Method used

By adding specific nitrogen compounds or linear amines to PLA as fluidizing additives, the shear viscosity of PLA is reduced, thereby improving the transparency of the film while maintaining good mechanical properties and biodegradability.

Benefits of technology

It is achieved to improve the optical transparency of the packaging film without damaging mechanical properties and biodegradability, and is particularly suitable for packaging of fruits and vegetables.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119836450A_ABST
    Figure CN119836450A_ABST
Patent Text Reader

Abstract

The invention relates to a highly transparent film comprising diacid and diol polyesters and lactic acid polyesters fluidized using a nitrogen component selected from the group consisting of nitrogen compounds of formula (I) or linear amines NH-R4-R5 as a fluidizing additive, and optionally cross-linking agent and / or chain extender # imgabs0 #
Need to check novelty before this filing date? Find Prior Art

Description

[0001] The present invention relates to a biodegradable film which is particularly suitable for the production of various types of packaging, in particular bags for transporting goods and bags for food packaging, such as bags for fruit and vegetables. This film, in addition to having good mechanical properties, in particular a high elastic modulus, also has particularly good optical transparency properties.

[0002] The production of packaging, in particular bags for food packaging (e.g. fruit and vegetable bags), requires the use of films that combine good mechanical properties with other properties that are beneficial to the consumer (e.g. optical transparency properties that allow the consumer to use the packaging to identify the object contained inside from the outside).

[0003] In the field of biodegradable packaging, in addition to mechanical and optical issues, there is a need to use materials that are able to degrade once their primary use has ended without generating waste accumulation in the environment.

[0004] Developing biodegradable films that combine these different properties is indeed a challenge, which requires balancing different, often highly inconsistent requirements. In fact, while specific criteria for mechanical properties and biodegradability can be achieved by using a material composition that shares each final film property according to its different characteristics, the achievement of high optical transparency properties is often particularly hindered by the heterogeneous properties of such a composition. For manufacturers of biodegradable packaging films, this means that they must decide whether to use a film with good mechanical and biodegradation properties and suboptimal optical transparency properties, or vice versa, to take advantage of aspects related to the optical properties of the packaging, thereby accepting lower performance in terms of mechanical and biodegradation properties.

[0005] It is known that the use of lactic acid polyester (PLA) or one of its esters is particularly important in polymer blends for obtaining highly transparent biodegradable films.

[0006] The use of fluid PLA is essential because it ensures good film transparency. Unfortunately, sufficiently fluid PLA is not always available on the market, since viscous PLA is easier and cheaper to produce. Therefore, there is a need to develop a strategy that allows these PLAs to be used in transparent grades, especially for fruits and vegetables, without compromising their optical properties.

[0007] The applicant has found a composition that achieves an excellent balance between optical properties, mechanical properties and high biodegradability. In this regard, reference is made to two patent applications WO2017216150 and WO2017216158.

[0008] However, there is no description of the fact that the transparency of the film is strongly dependent on the viscosity of the polyester component of lactic acid. In particular, as the viscosity of PLA increases, the transparency of the film decreases. Therefore, in order to obtain a film with good optical properties, PLA should have an optimal fluidity during extrusion of the formulation, i.e. a shear viscosity of less than 600 Pa.s (according to ASTM standard D3835, at T = 190 ° C, shear strain rate = 141.6 s -1 , D=1 mm, L / D=10, measured on dry material containing less than 400 ppm water).

[0009] It has surprisingly been found that in order to obtain PLA with optimal fluidity for the production of highly transparent films, sticky PLA can be used by using as a fluidizing additive the nitrogen component of a nitrogen compound or a linear amine NH-R4-R5 selected from formula (I):

[0010]

[0011] Where R1 and R2 can be OH or NH 2 , and R3 can be OH, NH 2 , C1-C4 alkyl or halogen, provided that if R1 and R2 are OH, then R3 is also OH;

[0012] Where R4 is C1-C4 alkyl and R5 is NH 2 Or C1-C4 alkyl.

[0013] Fluidized lactic acid polyester refers to lactic acid polyester whose shear viscosity has been reduced by adding nitrogen component, from 600 to 1700 Pa.s, preferably 900 to 1500 Pa.s shear viscosity (according to ASTM standard D3835, at T = 190 ° C, shear strain rate = 141.6s -1 , D=1 mm, L / D=10, measured on dry material containing less than 400 ppm water) to fluid lactic acid polyester.

[0014] Therefore, one object of the present invention is to prepare a film consisting of a composition comprising:

[0015] i) 65 to 89 wt.% of at least one polyester, compared to the total amount of components i. to iv., said polyester comprising:

[0016] a. relative to the total dicarboxylic acid component, containing the following dicarboxylic acid component:

[0017] a1) 0 to 60 mol % of units derived from at least one aromatic dicarboxylic acid;

[0018] a2) 40 to 100 mol % of units derived from at least one saturated aliphatic dicarboxylic acid;

[0019] a3) 0 to 5 mol % of units derived from at least one unsaturated aliphatic dicarboxylic acid;

[0020] b. relative to the total diol component, comprising the following diol components:

[0021] b1) 95 to 100 mol % of units derived from at least one saturated aliphatic diol;

[0022] b2) 0 to 5 mol % of units derived from at least one unsaturated aliphatic diol; and

[0023] ii) 10-34.995 wt% of one or more fluidized lactic acid polyesters relative to the total amount of components i.-iv.;

[0024] iii) 0.005-1 wt% of at least one nitrogen component selected from nitrogen compounds of formula (I) or linear amines NH-R4-R5, relative to the total amount of components i.-iv.:

[0025]

[0026] Where R1 and R2 can be OH or NH 2 , and R3 can be OH, NH 2 , C1-C4 alkyl or halogen, provided that if R1 and R2 are OH, then R3 is also OH;

[0027] Where R4 is C1-C4 alkyl and R5 is NH 2 or C1-C4 alkyl;

[0028] (iv) 0-1 wt% of at least one crosslinking agent and / or chain extender, compared to the total amount of components i.-iv.

[0029] In a particularly preferred aspect of the present invention, the film is composed of a polyester comprising an aromatic aliphatic polyester.

[0030] In a preferred aspect of the present invention, according to the results obtained in industrial scale tests, 1,3,5-triazine-2,4,6-triamine (formula (I), wherein R1, R2, R3 are NH 2 ) as the most effective fluidizing additive for producing fluidized lactic acid polyester from viscous PLA.

[0031] The invention also relates to various packages, in particular bags for transporting goods and bags for food packaging, such as bags for food and vegetables, comprising the film which may be single-layer or multi-layer. The multi-layer film is also particularly suitable for use as a ground film.

[0032] Another object of the present invention is to provide a method for preparing a suitable polymer composition for obtaining the above-mentioned film, the method comprising the following steps:

[0033] 1) Mixing:

[0034] (a) 85-99.9 wt% of one or more lactic acid polyesters characterized by a shear viscosity of 600 to 1700 Pa.s, preferably 900 to 1500 Pa.s (according to ASTM D 3835 standard, at T = 190 ° C, shear strain rate = 141.6 s -1 , D = 1 mm, L / D = 10, measured on dry material containing less than 400 ppm water), and

[0035] b) 15-0.1 wt% of at least one nitrogen component iii. selected from nitrogen compounds of formula (I) or linear amines NH-R4-R5, to obtain a fluidized lactic acid polyester:

[0036]

[0037] Where R1 and R2 can be OH or NH 2 , and R3 can be OH, NH 2 , C1-C4 alkyl or halogen, provided that if R1 and R2 are OH, then R3 is also OH;

[0038] Where R4 is C1-C4 alkyl and R5 is NH 2 Or C1-C4 alkyl.

[0039] 2) mixing the fluidized lactic acid polyester with at least one polyester i.

[0040] Unless otherwise defined, all terms, symbols and other scientific terms in the art used herein are intended to have the meanings commonly understood by those skilled in the art to which this specification belongs. In some cases, for clarity and / or ease of reference, terms with commonly understood meanings are defined herein; therefore, the inclusion of such definitions in this specification should not be interpreted as representing a substantial difference from what is commonly understood in the art.

[0041] The terms "comprising," "having," "including," and "containing" should be construed as open-ended terms (i.e., meaning "including, but not limited to,") and should also be construed as support for terms such as "consisting essentially of," "consisting essentially of," "consisting of," or "consisting of."

[0042] The terms "consisting essentially of" and "consisting essentially of" should be understood as semi-closed terms, meaning that other ingredients that affect the novel characteristics of the present invention are not included (thus, optional excipients may be included).

[0043] The terms “consisting of” and “composed of” are to be understood as closed terms.

[0044] Although the present invention is susceptible to various alternative modifications, many preferred embodiments are described in detail below. However, it should be understood that it is not intended to limit the present invention to the specific embodiments shown, but on the contrary, the present invention is intended to cover all modifications, substitutions and equivalents falling within the scope of the present invention defined by the claims.

[0045] Unless otherwise stated, the use of "such as", "etc", "or" indicates non-exclusive alternatives without limitation. Unless otherwise stated, the use of "including" means "including but not limited to".

[0046] As regards component i of the composition that is the subject of the invention, it is present in an amount ranging from 65 to 89% by weight, preferably from 70 to 85% by weight, even more preferably from 74 to 81% by weight, relative to the total amount of components i to iv.

[0047] The aromatic dicarboxylic acid in component a1 is preferably selected from aromatic dicarboxylic acids of the phthalic acid type, preferably terephthalic acid or isophthalic acid and esters, salts and mixtures thereof, more preferably terephthalic acid.

[0048] In a particularly preferred form, component a1 is terephthalic acid and its esters, salts and mixtures.

[0049] The aromatic dicarboxylic acid in component a1 is present in 0-60 mol %, preferably 40-60 mol %, more preferably 42-52 mol %, even more preferably 45-49 mol %, relative to the total dicarboxylic acid components.

[0050] The saturated aliphatic dicarboxylic acids in component a2 are preferably selected from saturated C2-C24, preferably C4-C13, more preferably C4-C11 dicarboxylic acids, their C1-C24, preferably C1-C4 alkyl esters, their salts and mixtures thereof. Preferably, the saturated aliphatic dicarboxylic acids are selected from succinic acid, 2-ethylsuccinic acid, glutaric acid, 2-methylglutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, undecanedioic acid, dodecanedioic acid, tridecanedioic acid and C1-24 alkyl esters thereof. In a preferred embodiment of the present invention, the saturated aliphatic dicarboxylic acids comprise a mixture, the mixture comprising at least 50 mol%, preferably greater than 60 mol%, more preferably greater than 65 mol% of succinic acid, adipic acid, azelaic acid, sebacic acid, tridecanedioic acid, their C1-C24 alkyl esters, preferably C1-C4 alkyl esters and mixtures thereof. In a particularly preferred embodiment, the mixture comprises or consists of adipic acid and azelaic acid and contains azelaic acid in an amount of 5 to 65 mol %, more preferably 10 to 35 mol %, relative to the total amount of adipic acid and azelaic acid. In a further particularly preferred form, when component a1 is 0, component a2 is succinic acid.

[0051] The unsaturated aliphatic dicarboxylic acid in component a3 is preferably selected from itaconic acid, fumaric acid, 4-methylene-pimelic acid, 3,4-bis(methylene)azelaic acid, 5-methylene-azelaic acid, their C1-C24, preferably C1-C4 alkyl esters, their salts and mixtures thereof. In a preferred embodiment of the present invention, the unsaturated aliphatic dicarboxylic acid comprises a mixture containing at least 50 mol%, preferably greater than 60 mol%, more preferably greater than 65 mol% of itaconic acid and its C1-C24, preferably C1-C4 esters. More preferably, the unsaturated aliphatic dicarboxylic acid consists of itaconic acid.

[0052] As for the saturated aliphatic diols in component b1, they are preferably selected from 1,2-ethanediol, 1,2-propylene glycol, 1,3-propylene glycol, 1,4-butylene glycol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, 1,11-undecanediol, 1,12-dodecanediol, 1,13-tridecanediol, 1,4-cyclohexanedimethanol, neopentyl glycol, 2-methyl-1,3-propanediol, dianhydrosorbitol, dianhydromannitol, dianhydroiditol, cyclohexanediol, cyclohexanemethanediol, dialkylene glycols and polyalkylene glycols having a molecular weight of 100 to 4000, such as polyethylene glycol, polypropylene glycol, and mixtures thereof. Preferably, the diol component comprises at least 50 mol% of one or more diols selected from 1,2-ethylene glycol, 1,3-propylene glycol, 1,4-butanediol, More preferably, the diol component comprises or consists of 1,4-butanediol.

[0053] As for the unsaturated aliphatic diols in component b2, they are preferably selected from cis-2-butene-1,4-diol, trans-2-butene-1,4-diol, 2-butyne-1,4-diol, cis-2-pentene-1,5-diol, trans-2-pentene-1,5-diol, 2-pentyne-1,5-diol, cis-2-hexene-1,6-diol, trans-2-hexene-1,6-diol, 2-hexyne-1,6-diol, cis-3-hexene-1,6-diol, trans-3-hexene-1,6-diol, 3-hexene-1,6-diol.

[0054] The molecular weight Mn of the polyester i is preferably higher than 20 000, more preferably higher than 40 000. As regards the polydispersity index Mw / Mn of the molecular weight, it is preferably from 1.5 to 10, more preferably from 1.6 to 5.0 and even more preferably from 1.8 to 2.7.

[0055] The molecular weights Mn and Mw can be measured by gel permeation chromatography (GPC). The determination can be performed using a chromatography system maintained at 40°C, using a set of two columns in series (particle size 5 μm and 3 μm, with mixed porosity), a refractive index detector, chloroform as eluent (flow rate 0.5 mL / min) and using polystyrene as a reference standard.

[0056] Preferably, the polyester i. has an intrinsic viscosity greater than 0.3 dl / g (using an Ubbelohde viscometer in CHCl 3 The concentration of the aqueous solution is 0.2 g / dl (measured at 25°C), preferably 0.3 to 2.0 dl / g, more preferably 0.4 to 1.2 dl / g.

[0057] The polyester i. preferably has a terminal acid group content of less than 100 meq / kg, preferably less than 60 meq / kg, even more preferably less than 40 meq / kg.

[0058] The content of terminal acid groups can be measured as known in the art, for example as shown in WO2017216150.

[0059] The polyester i. is biodegradable. In the meaning of the present invention, a biodegradable polymer is a polymer that is biodegradable according to EN 13432:2002.

[0060] The polyester i. contained in the film according to the invention can be synthesized according to any method known in the prior art. In particular, it can be advantageously obtained using a polycondensation reaction.

[0061] Advantageously, the synthesis process can be carried out in the presence of a suitable catalyst. Examples of suitable catalysts include organometallic tin compounds, such as stannic acid derivatives, titanium compounds, such as n-butyl titanate, aluminum compounds, such as triisopropylaluminum, antimony, zinc and zirconium compounds and mixtures thereof.

[0062] As regards component ii. of the film according to the invention, it comprises, relative to the total amount of components i-iv., 10 to 34.995 wt%, preferably 14 to 29.995 wt%, even more preferably 18 to 25.995 wt% of one or more fluidized lactic acid polyesters.

[0063] In a preferred embodiment, the lactic acid polyester is selected from poly-L-lactic acid, poly-D-lactic acid, poly-DL-lactic acid stereocomplexes, copolymers containing more than 50 wt% of said lactic acid polyesters or mixtures thereof. Particularly preferred are lactic acid polyesters containing at least 95 wt% of repeating units derived from L-lactic acid or D-lactic acid or mixtures thereof, having a shear viscosity of 600 to 1700 Pa.s, preferably 900 to 1500 Pa.s (according to ASTM standard D3835, at T = 190 ° C, shear strain rate = 141.6 s -1 , D=1 mm, L / D=10, measured on dry material containing less than 400 ppm water).

[0064] In a particularly preferred embodiment of the present invention, the lactic acid polyester comprises at least 95 wt% of units derived from L-lactic acid, <5% of repeating units derived from D-lactic acid, has a melting point of 135-180°C, and a glass transition temperature (Tg) in the range of 45-75°C. Commercial examples of lactic acid polyesters having these properties include the biopolymer product Ingeo TM 4043D and Ingeo TM 4032D.

[0065] As for component iii of the present invention, it contains, based on the total amount of components i. to iv., 0.005 to 1 wt%, preferably 0.005 to 0.1 wt%, even more preferably 0.005 to 0.05 wt% of at least one nitrogen component selected from nitrogen compounds of formula (I) or linear amines NH-R4-R5:

[0066]

[0067] Where R1 and R2 can be OH or NH 2 , and R3 can be OH, NH 2 , C1-C4 alkyl or halogen, provided that if R1 and R2 are OH, then R3 is also OH;

[0068] Where R4 is C1-C4 alkyl and R5 is NH 2Or C1-C4 alkyl.

[0069] The content of component iii in the film can be determined using analytical methods known in the art, such as HPLC analysis of an aqueous solution prepared as follows:

[0070] 500 mg of sample was placed in a screw cap vial along with 15 mL of 1% HCOOH aqueous solution;

[0071] Incubate in an oven at 70°C for 1 night;

[0072] 1 mL of the aqueous solution was filtered through a 0.2 μm RC filter and injected into the HPLC as is;

[0073] • The amount is determined with the aid of a calibration line obtained by injecting component iii. in a concentration range of 1 μg / ml to 10 μg / ml.

[0074] Preferred component iii. A nitrogen compound corresponding to the general formula (I), wherein R1, R2, R3 are NH 2 or its derivatives.

[0075] In the film composition according to the invention, preferably 0 to 0.5 wt. % of at least one crosslinker and / or chain extender is also present, relative to the total amount of components i.-iv., to improve the hydrolytic stability (component iv.).

[0076] The crosslinking agent and / or chain extender is selected from difunctional and / or polyfunctional compounds carrying isocyanate, peroxide, carbodiimide, isocyanurate, oxazoline, epoxy, anhydride or divinyl ether groups or mixtures thereof.

[0077] Particularly preferred are mixtures of difunctional and / or polyfunctional compounds carrying isocyanate groups and difunctional and / or polyfunctional compounds carrying epoxy groups, even more preferably comprising at least 75% w / w of difunctional and / or polyfunctional compounds carrying isocyanate groups.

[0078] The compounds having di- and polyfunctional groups (including isocyanate groups) are preferably selected from p-phenylene diisocyanate, 2,4-toluene diisocyanate, 2,6-toluene diisocyanate, 4,4-diphenylmethane diisocyanate, 1,3-phenylene-4-chlorodiisocyanate, 1,5-naphthalene diisocyanate, 4,4-diphenylene diisocyanate, 3,3'-dimethyl-4,4-diphenylmethane diisocyanate, 3-methyl-4,4'-diphenylmethane diisocyanate, ... Phenyl ester diisocyanate, 2,4-cyclohexane diisocyanate, 2,3-cyclohexane diisocyanate, 1-methyl 2,4-cyclohexyl diisocyanate, 1-methyl 2,6-cyclohexyl diisocyanate, bis-(isocyanate cyclohexyl) methane, 2,4,6-toluene triisocyanate, 2,4,4-diphenyl ether triisocyanate, polymethylene-polyphenyl-polyisocyanate, methylene diphenyl diisocyanate, triphenylmethane triisocyanate, 3,3'-dithiolylene-4,4-diisocyanate, 4,4'-methylenebis(2-methylphenylisocyanate), hexamethylene-1,3-cyclohexylene diisocyanate, 1,2-cyclohexylene diisocyanate and mixtures thereof. In a preferred embodiment, the compound containing an isocyanate group is 4,4-diphenylmethane-diisocyanate.

[0079] As regards difunctional and polyfunctional compounds bearing peroxide groups, these are preferably selected from benzoyl peroxide, lauroyl peroxide, isononanoyl peroxide, di-(tert-butylperoxyisopropyl)benzene, tert-butyl peroxide, dicumyl peroxide, α,α-di-(tert-butylperoxy)diisopropylbenzene, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane, tert-butylcumyl peroxide, di-tert-butyl peroxide, 2,5-dimethyl-2,5-di(tert-butylperoxy)hex-3-yne, di(4-tert-butylcyclohexyl)peroxydicarbonate, dicetyl peroxydicarbonate, dimyristyl peroxydicarbonate, 3,6,9-triethyl-3,6,9-trimethyl-1,4,7-triperoxynonane, di(2-ethylhexyl)peroxydicarbonate and mixtures thereof.

[0080] The difunctional and polyfunctional compounds with carbodiimide groups preferably used in the composition according to the invention are selected from the group consisting of poly(cyclooctylenecarbodiimide), poly(1,4-dimethylenecyclohexylenecarbodiimide), poly(cyclohexylenecarbodiimide), poly(ethylenecarbodiimide), poly(butylenecarbodiimide), poly(isobutylenecarbodiimide), poly(nonylenecarbodiimide), poly(dodecylenecarbodiimide), poly(neopentylenecarbodiimide), poly(1,4-dimethylenephenylenecarbodiimide), poly(2,2′,6,6′-tetraisopropyldiphenylenecarbodiimide) (S tabaxol D), poly (2,4,6-triisopropyl-1,3-phenylene carbodiimide) (S tabaxol P-100), poly (2,6-diisopropyl-1,3-phenylene carbodiimide) (S tabaxol PP), poly(tolylcarbodiimide), poly(4,4'-diphenylmethanecarbodiimide), poly(3,3'-dimethyl-4,4'-biphenylenecarbodiimide), poly(p-phenylenecarbodiimide), poly(m-phenylenecarbodiimide), poly(3,3'-dimethyl-4,4'-diphenylmethanecarbodiimide), poly(naphthylenecarbodiimide), poly(isophoronecarbodiimide), poly(cumylenecarbodiimide), p-phenylenebis(ethylcarbodiimide), 1,6-hexamethylenebis(ethylcarbodiimide), 1,8-octamethylenebis(ethylcarbodiimide), 1,10-decamethylenebis(ethylcarbodiimide), 1,12-decamethylenebis(ethylcarbodiimide) and mixtures thereof.

[0081] Examples of difunctional and polyfunctional compounds carrying epoxy groups which can be advantageously used in the composition according to the invention are all polyepoxides from epoxidized oils and / or from styrene-glycidyl ether-methyl methacrylate or glycidyl ether-methyl methacrylate having a molecular weight in the range from 1000 to 10000 and an epoxide number per molecule of from 1 to 30 and preferably from 5 to 25, the epoxides being selected from the group consisting of diethylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, polyglycerol polyglycidyl ether, 2-butylene oxide, polyglycerol polyglycidyl ether, isoprene diepoxide and cycloaliphatic diepoxides, 1,4-cyclohexanedimethanol diglycidyl ether, glycidyl 2-methylphenyl ether, glyceryl propoxy triglycidyl ether, glyceryl propoxy triglycidyl ether, tetraglycidyl ether of meta-xylene diamine and diglycidyl ether of bisphenol A and mixtures thereof.

[0082] Catalysts can also be used with difunctional and polyfunctional compounds bearing isocyanate, peroxide, carbodiimide, isocyanurate, oxazoline, epoxide, anhydride and divinyl ether groups, such as those mentioned above, to increase the reactivity of the reactive groups. In the case of polyepoxides, fatty acid salts can be used, even more preferably calcium stearate and zinc stearate.

[0083] In a particularly preferred embodiment of the invention, the crosslinker and / or chain extender comprises a compound with isocyanate groups, preferably 4,4-diphenylmethane diisocyanate, and / or a compound with carbodiimide groups and / or with epoxy groups, preferably of the styrene-glycidyl p-methylmethacrylate type.

[0084] As mentioned above, it has been determined that film transparency is strongly dependent on the viscosity of the PLA used. As can be seen in Table 1 below, as the shear viscosity increases (less than 600 Pa.s - according to ASTM D3835 standard at T = 190 ° C, shear strain rate = 141.6s -1 , D=1 mm, L / D=10, measured on dry material containing less than 400 ppm water), the formulation starts to become opaque.

[0085] In an OMC EBV60 / 36 twin-screw extruder (L / D=36; diameter 58 mm), the following conditions were used:

[0086] Screw diameter (D) = 58 mm;

[0087] L / D = 36;

[0088] Screw rotation = 140 rpm;

[0089] Temperature distribution = 60-150-180-210×4-150×2℃;

[0090] ·Throughput: 40kg / h;

[0091] • Vacuum degassing in zone 8 of 10 zones.

[0092] mix:

[0093] 79.90% poly(butylene adipate-co-butylene terephthalate) having a terephthalic acid content of 47.3 mol% relative to the total amount of total dicarboxylic acids, MFR 4.8 g / 10 min (@190°C, 2.16 kg) and an acidity of 37 meq / kg

[0094] 19.75% PLA having the characteristics described in Tables 1 and 2,

[0095] 0.25% of a styrene-alkyl acrylate-glycidyl methacrylate random copolymer having an Mw of 6800 and an epoxy value of 10 per molecule,

[0096] 0.10% erucamide.

[0097] The resulting composition was fed into a Ghioldi type blown film machine with a 40 mm diameter screw and L / D 30 operating at 64 rpm with a thermal profile of 120-170-170×7°C. The film forming head with an air gap of 0.9 mm and L / D 12 was set at 170°C. Film forming was performed with a blow ratio of 4.5 and a stretch ratio of 14.5. This resulted in a film thickness of 14 μm.

[0098] Table 1

[0099] membrane Shear viscosity of PLA used (Pa.s) Thickness(μm) T(%) H(%) C(%) 1 219 14 92 10 90 2 230 14 91 9 95 3 551 14 90 14 90 4 776 14 90 32 69 5 1239 14 90 73 14

[0100] It has also been determined that the transparency of the film depends on the composition ratio of the mixture of fluid polylactic acid and viscous polylactic acid.

[0101] PLA fluid: Ingeo 3251D polylactic acid [according to ASTM D3835 standard, at T = 190 ° C, shear strain rate = 141.6 s -1 , D = 1 mm, L / D = 10, measured on dry material containing less than 400 ppm water, equivalent to 219 Pa.s].

[0102] Viscous PLA: Ingeo 4043D polylactic acid [according to ASTM D3835 standard, at T = 190 ° C, shear strain rate = 141.6 s -1 , D = 1 mm, L / D = 10, measured on dry material containing less than 400 ppm water, equivalent to 1239 Pa.s].

[0103] As can be seen from Table 2, as the percentage of the fluid polylactic acid component decreases, the transparency of the film decreases.

[0104] Table 2

[0105]

[0106] Therefore, it is necessary to find a way to improve the optical properties of films starting from viscous PLA, i.e. films with a shear viscosity of 600 to 1700 Pa.s (according to ASTM standard D3835, at T = 190°C, shear strain rate = 141.6 s -1 , D = 1 mm, L / D = 10, measured on dry material containing less than 400 ppm water). As can be seen in Table 3, it is not a trivial matter to find additives that can modify the flowability of PLA to obtain films with satisfactory optical properties.

[0107] The starting PLA was characterized by an MFI of 3.6 g / 10 min at 190° C. and 2.16 kg. The different molecules were added to an OMC EBV60 / 36 twin-screw extruder (L / D=36; diameter 58 mm) operating under the following conditions:

[0108] Screw diameter (D) = 58 mm;

[0109] L / D = 36;

[0110] Screw rotation = 140 rpm;

[0111] Heat distribution = 60-150-180-210×4-150×2℃;

[0112] ·Throughput: 40kg / h;

[0113] • Vacuum degassing in zone 8 of 10 zones.

[0114] Table 3

[0115]

[0116]

[0117] According to Table 3, only nitrogen compounds of formula (I) such as 1,3,5-triazine-2,4,5-triamine work to give good MFI for PLA. Note that the presence of phenyl in R3 and NH in R1 and R2 2 The very similar structure of the nitrogen compound of formula (I) does not work at all.

[0118] Input of 1% w / w citric acid additive yielded a PLA with a shear viscosity of 620 Pa.s, while addition of 0.3% 1,3,5,5-triazine-2,4,6-triamine resulted in a shear viscosity of 241 Pa.s (both according to ASTM standard D3835, at T = 190 °C, shear strain rate = 141.6 s -1 , D = 1 mm, L / D = 10, measured on a dry material containing less than 400 ppm of water). Therefore, using 1,3,5-triazine-2,4,6-triamine, a PLA with a shear viscosity of less than 600 Pa.s can be obtained with an addition concentration of less than 1%. The fluid PLA thus obtained has a residual content of 1,3,5-triazine-2,4,6-triamine of 0.09% (measured by HPLC according to the method given in the description).

[0119] The shelf life of fluidized PLA was checked by natural aging of the stored granules after drying. After 2 months, the change in MFI (measured according to ISO 1133-1 at 190°C and 2.16 kg) was found to be less than 5% compared to the initial value. Therefore, it has been demonstrated that PLA is stable over time after fluidization.

[0120] The monolayer film may be prepared according to any method known in the art, such as film blowing or cast extrusion.

[0121] The multilayer film can be prepared according to any method known in the art, for example by coextrusion, coating or lamination processes. In a preferred embodiment, the film according to the invention can be obtained by a coextrusion process, which is preferably associated with a bubble film forming process.

[0122] This makes it particularly suitable for producing a wide range of articles, such as various packaging, in particular bags for transporting goods and bags for food packaging, such as fruit and vegetable bags, which comprise the multilayer film. It is also particularly suitable for ground films.

[0123] As regards the optical properties (relating to a film thickness of 14 microns), the light transmittance values ​​are higher than 90%, more preferably higher than 91%, the haze (turbidity) values ​​are lower than 30%, more preferably lower than 25%, even more preferably lower than 20%, still more preferably lower than 15%, and the transparency (sharpness) is greater than 70%, more preferably greater than 75%, more preferably greater than 85%, yet more preferably greater than 90% (measured according to ASTM D1003), making the films according to the invention particularly suitable for the above-mentioned applications.

[0124] The films according to the invention are biodegradable and disintegrable under industrial composting conditions according to EN 13432:2002.

[0125] Detailed examples of the solution discovered by the applicant will be given below, which examples should not be considered limiting.

[0126] The invention thus conceived is susceptible of numerous modifications and variations, all of which are within the scope of the invention as set forth in the appended claims.

[0127] Component i: poly(butylene adipate-co-butylene terephthalate) having a terephthalic acid content of 47.3 mol% relative to the total amount of total dicarboxylic acids, an MFR of 4.8 g / 10 min (@190° C., 2.16 kg), and an acidity of 37 meq / kg.

[0128] PLA-1: Polylactic acid Ingeo 4032D, [according to ASTM standard D3835, at T = 190 ° C, shear strain rate = 141.6 s -1 , D=1 mm, L / D=10, the shear viscosity measured on dry material containing less than 400 ppm of water is equal to 1428 Pa.s].

[0129] PLA-2: Polylactic acid Ingeo 3251D, [according to ASTM standard D3835, at T = 190 ° C, shear strain rate = 141.6 s -1 , D=1 mm, L / D=10, the shear viscosity measured on dry material containing less than 400 ppm of water is equal to 219 Pa.s].

[0130] Component iii: 1,3,5-triazine-2,4,6-triamine

[0131] Component iv: Styrene-alkyl acrylate-glycidyl methacrylate random copolymer having a Mw of 6800 and an epoxy value of 10 per molecule

[0132] Example 1 - Membrane Preparation

[0133] In Example 1, the lactic acid polyester was pre-blended with component iii under the same conditions as the blends shown in Table 3, wherein the lactic acid polyester PLA-1 was 99.70 wt% of the weight of the composition, and iv was 0.3%. The resulting fluidized lactic acid polyester (mixture 1a) was characterized by a shear strain rate of 141.6 s at T = 190 ° C according to ASTM standard D3835. -1 , D = 1 mm, L / D = 10, the shear viscosity measured on dry material containing less than 400 ppm water is 241 Pa.s.

[0134] In Example 2, the lactic acid polyester was pre-blended with component iii under the same conditions as the blends shown in Table 3, wherein the lactic acid polyester PLA-1 was 90 wt% of the weight of the composition and iv was 10%, except that the thermal profile was set to 60-150-160×5-150×2° C. The fluidized lactic acid polyester obtained (mixture 1b) is characterized by a shear viscosity of 88 Pa.s, which is 0.0447 W / m according to ASTM standard D3835 at T=190° C., shear strain rate=141.6 s -1 , D=1 mm, L / D=10, measured on dry material containing less than 400 ppm water.

[0135] Composition preparation: The composition described in Table 4 was fed to an OMC EBV60 / 36 twin-screw extruder (L / D=36; diameter 58 mm) and operated under the following conditions:

[0136] Screw diameter (D) = 58 mm;

[0137] L / D=36;

[0138] Screw rotation = 140 rpm;

[0139] Temperature distribution = 60-150-180-210x4-150x2°C;

[0140] Capacity: 40kg / h;

[0141] Zone 8 of the 10 zones was vacuum degassed.

[0142] Film preparation: The resulting composition was fed into a Ghioldi type blown film machine with a 40 mm diameter screw and L / D 30 operating at 64 rpm with a heat profile of 120-170-170×7°C. The film forming head with an air gap of 0.9 mm and L / D 12 was set at 170°C. Film formation was performed with a blow ratio of 4.5 and a stretch ratio of 14.5. This resulted in a film thickness of 14 μm.

[0143] Table 4 Composition of the mixture (wt%)

[0144] i PLA-1 PLA-2 Mixture 1a Mixture 1b iv Example 1 79.60 - - 20 - 0.25 Example 2 79.60 18.45 - - 0.55 0.25 Comparative Example 1 79.75 20 - - - 0.25 Comparative Example 2 79.75 - 20 - - 0.25

[0145] In Table 4 we show a viscous lactic acid polyester (PLA-1) and a fluid lactic acid polyester (PLA-2). The viscous lactic acid polyester was combined with two different mixtures containing a nitrogen compound of formula (I).

[0146] Table 5 Results of optical properties

[0147]

[0148]

[0149] As can be seen from Table 5, the viscous acid lactic acid polyester (PLA-1, comparative example 1) without the presence of the nitrogen compound of formula (I) gives very poor optical results. In contrast, the viscous acid lactic acid polyester PLA-1 gives good optical results only when combined with the nitrogen compound of formula (I) (Example 1 and Example 2). Comparative example 2, which does not contain the nitrogen compound of formula (I) and has a fluid acid lactic acid polyester, shows the results to be achieved.

[0150] HPLC analysis by the method specified in the description showed that the concentration of 1,3,5-triazine-2,4,6-triamine in the film corresponding to Example 1 was 0.007% w / w, and the concentration of 1,3,5-triazine-2,4,6-triamine in the film corresponding to Example 2 was 0.022% w / w.

[0151] Example 3 (Comparative Example)

[0152] Amide waxes, such as erucamide (C 22 H 43NO, primary fatty amides produced by the formal condensation of the carboxyl groups of erucic acid with ammonia) do not allow fluidized lactic acid polyesters to be obtained starting from lactic acid polyesters characterized by a shear viscosity of 600 to 1700 Pa.s. In particular, starting from a lactic acid polyester characterized by a shear viscosity of 1239 Pa.s, a lactic acid polyester with a shear viscosity of 1044 Pas is obtained by extrusion addition of 0.5% w / w of erucamide, while a lactic acid polyester with a shear viscosity of 948 Pas is obtained by extrusion addition of 1% w / w of erucamide. The shear viscosity values ​​obtained are much higher than 600 Pa.s, so the lactic acid polyester cannot be considered fluidized. According to ASTM standard D3835, at T = 190°C, shear strain rate = 141.6s -1 The shear viscosity was measured at 100 % RH, D = 1 mm, L / D = 10 on dry material containing less than 400 ppm water. The twin screw operating conditions correspond to those reported for the compounds described in Table 3.

Claims

1. A film consisting of a polymer composition, the polymer composition comprising: i) 65 to 89 wt.% of at least one polyester, compared to the total amount of components i. to iv., said polyester comprising: a. relative to the total dicarboxylic acid component, containing the following dicarboxylic acid component: a1) 0 to 60 mol % of units derived from at least one aromatic dicarboxylic acid; a2) 40 to 100 mol % of units derived from at least one saturated aliphatic dicarboxylic acid; a3) 0 to 5 mol % of units derived from at least one unsaturated aliphatic dicarboxylic acid; b. relative to the total diol component, comprising the following diol components: b1) 95 to 100 mol % of units derived from at least one saturated aliphatic diol; b2) 0 to 5 mol % of units derived from at least one unsaturated aliphatic diol; and ii) 10-34.995 wt% of one or more fluidized lactic acid polyesters relative to the total amount of components i.-iv.; iii) 0.005-1 wt% of at least one nitrogen component selected from nitrogen compounds of formula (I) or linear amines NH-R4-R5, relative to the total amount of components i.-iv.: wherein R1 and R2 may be OH or NH2, and R3 may be OH, NH2, C1-C4 alkyl or halogen, provided that if R1 and R2 are OH, then R3 is also OH; wherein R4 is C1-C4 alkyl and R5 is NH2 or C1-C4 alkyl; (iv) 0-1 wt% of at least one crosslinking agent and / or chain extender, compared to the total amount of components i.-iv.

2. The film according to claim 1, wherein the aromatic dicarboxylic acid in component a1) is preferably selected from aromatic dicarboxylic acids of the phthalic acid type, preferably terephthalic acid or isophthalic acid, more preferably terephthalic acid, their esters, salts and mixtures thereof.

3. The film according to any one of the preceding claims, wherein the saturated aliphatic dicarboxylic acid in component a2) is preferably selected from saturated C2-C24, preferably C4-C13, more preferably C4-C11 dicarboxylic acids, their C1-C24 alkyl esters, more preferably C1-C4 alkyl esters, their salts and mixtures thereof.

4. The film according to claim 3, wherein the saturated aliphatic dicarboxylic acid in component a2) is selected from succinic acid, 2-ethylsuccinic acid, glutaric acid, 2-methylglutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, undecanedioic acid, dodecanedioic acid, tridecanedioic acid and their C1-24 alkyl esters.

5. The film according to claim 3, wherein the saturated aliphatic dicarboxylic acid comprises a mixture comprising at least 50 mol%, preferably greater than 60 mol%, more preferably greater than 65 mol% of succinic acid, adipic acid, azelaic acid, sebacic acid, tridecanedioic acid, their C1-C24 alkyl esters, preferably C1-C4 alkyl esters, their salts and mixtures thereof.

6. The film according to claim 3, wherein the mixture of saturated carboxylic acids comprises or consists of adipic acid and azelaic acid and contains azelaic acid in an amount of 5 to 65 mol %, more preferably 10 to 35 mol %, relative to the total amount of adipic acid and azelaic acid.

7. The film according to claim 3, wherein when component a1) is equal to 0, the dicarboxylic acid a2) is succinic acid.

8. The membrane of claim 1, wherein the nitrogen component (iii) is a product of the general formula (I), wherein R1, R2, R3 are NH2 or derivatives thereof.

9. The membrane according to claim 1, wherein component iv comprises at least one difunctional and / or polyfunctional compound bearing isocyanate, peroxide, carbodiimide, isocyanurate, oxazoline, epoxide, anhydride, divinyl ether groups and mixtures thereof.

10. A package comprising a film according to any one of the preceding claims.

11. The package according to claim 10, selected from bags for transporting goods and bags for food packaging, such as bags for fruit and vegetables.

12. A method for preparing a polymer composition suitable for obtaining the film according to claim 1, comprising the steps of: 1) Mixing: a) 85-99.9 wt% of one or more lactic acid polyesters characterized by a shear viscosity of 600 to 1700 Pa.s, preferably 900 to 1500 Pa.s (according to ASTM D 3835 standard, at T = 190 ° C, shear strain rate = 141.6 s -1 , D = 1 mm, L / D = 10, measured on dry material containing less than 400 ppm water), and b) 15-0.1 wt% of at least one nitrogen component iii. selected from nitrogen compounds of formula (I) or linear amines NH-R4-R5, to obtain a fluidized lactic acid polyester: wherein R1 and R2 may be OH or NH2, and R3 may be OH, NH2, C1-C4 alkyl or halogen, provided that if R1 and R2 are OH, then R3 is also OH; wherein R4 is C1-C4 alkyl and R5 is NH2 or C1-C4 alkyl; 2) mixing the fluidized lactic acid polyester with at least one polyester i.

13. The method according to claim 12, further characterized in that in step 1, the nitrogen content of component iii. is 1 to 15 wt%, and the mixture in step 2 further comprises one or more lactic acid polyesters characterized by a shear viscosity of 600-1700 Pa.s, preferably 900-1500 Pa.s (according to ASTM standard D3835, at T = 190 ° C, shear strain rate = 141.6 s -1 , D=1 mm, L / D=10, measured on dry material containing less than 400 ppm water).

Citation Information

Patent Citations

  • Multilayer biodegradable film

    WO2017216150A1

  • Biodegradable film

    WO2017216158A1